The Politics of Contemporary Publishing in India — Ought we to be Excited, Concerned or Despairing? - Butalia, Urvashi (JOURNAL OF INDIAN EDUCATION, 2014)
The Indian publishing scene is widely acknowledged to be vibrant and dynamic today, and indeed, it is both complex and varied. After having adopted a policy of self reliance and indigenism in the years after Indpendence, the publishing sector today, like much else in the country, has opened up to foreign investment and some of the largest publishing houses in the world have a presence here. Is this a new form of colonialism? Should we be concerned about it or should we take it as inevitable? What will the presence of multinationals mean for indigenous publishing in India, and will English publishing, which seems to be dominant, outstrip Indian language publishing? How can Indian publishing hold its own, and should it do so at all? Where, if at all, do the excitements lie? Do independent publishers have anything to offer? Tracing her own entry into the world of publishing more than three decades ago, Butalia will focus, in this talk, on what has changed, both within the industry, and in the external conditions that impinge on it, and make an examination of whether this change has been positive or negative or a mix of the two. She will argue that the production of knowledge is a political act, and that the Indian State has done little or nothing to help the publishing industry produce books, and therefore knowledge, in order to reach the continuing hunger for it among Indians. She will further show how it is here that the contributions of the small independent publisher need to be recognised and supported.